1985
DOI: 10.1123/jtpe.4.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Direct, Indirect, and Noncontributing Teacher Behavior

Abstract: The purpose of this study was to investigate the variation in teaching behavior of physical educators over an instructional unit. Both inter- and intra-comparisons were made for three experienced teachers. The subjects recorded audiotapes during each of 10 lessons in a volleyball unit. The directly, indirectly, and noncontributing behaviors for each teacher were coded and described by Observation System for Content Development-Physical Education (OSCD-PE). The results indicate that most teaching behaviors were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…Deciding what content to teach and how to sequence that content is a central task of teaching, yet the scholarly literature in physical education indicates little about teachers' progressions or their rationales for their choices. Rink (1983) and Gusthart (1985) reported that teachers' use of informing, refining, extending, and applying tasks varied across teachers. Petersen (1991) found that teachers' content progressions were influenced by children's affective responses such as enjoyment, boredom, and interest and by children's ability to manage the social aspects of the activity.…”
Section: Research On Content Progression In Physical Educationmentioning
confidence: 99%
“…Deciding what content to teach and how to sequence that content is a central task of teaching, yet the scholarly literature in physical education indicates little about teachers' progressions or their rationales for their choices. Rink (1983) and Gusthart (1985) reported that teachers' use of informing, refining, extending, and applying tasks varied across teachers. Petersen (1991) found that teachers' content progressions were influenced by children's affective responses such as enjoyment, boredom, and interest and by children's ability to manage the social aspects of the activity.…”
Section: Research On Content Progression In Physical Educationmentioning
confidence: 99%
“…Schempp supports his position on the instability of teacher behavior with the work of Rink (1983) and Gusthart (1985). Both studies demonstrated how teaching behavior variedwith context.…”
mentioning
confidence: 67%
“…Given the critical role of content development in teaching, several scholars have focused on this line of research during the last three decades. Studies using Rink’s (2010) content development categories have found that informing tasks occurred at different parts of a unit but decreased in number and were replaced at the end of the unit by applying tasks (Dervent et al, 2018); additionally, they were usually combined with few refining tasks before proceeding to games (Gusthart, 1985; Jones, 1992; Siedentop et al, 1994; Ward et al, 2015). However, evidence also suggests that this combination is not always associated with children's learning (Ayvazo and Ward, 2011).…”
Section: Introductionmentioning
confidence: 99%